التشخيص المالي و تأثيره على المالية السلوكية - بوشليل, صابرية (My University, 2022)
This research paper aims to shed light on the most important means and tools in the process of financial diagnosis, which are financial analysis, and it also has another term, namely, fundamental analysis and also one of the financial diagnostic tools, technical (technical) analysis and the last type is psychological analysis, But in terms of arranging the information in this research paper, it was placed with another element, which is behavioural finance, which studies the behaviour of the investor and the problems that the investor suffers from in the financial markets, especially the lack of transparency of the included information or the process of amplifying the information, as well as the lack of investor guidance. That is why we have referred in this research to the financial markets and all their related information, as well as how the investor enters the stock exchange, the problems that the investor suffers from, and how to deal in the stock market as a successful investor. This research paper comes to show the role of financial diagnosis and the extent of its impact on behavioural finance, and this is related to the stock market (the stock market.(
دراسة حالة بورصة الجزائر
Keywords: المالية السلوكية, التحليل المالي, الأسواق المالية, علم النفس ,الإستثمار